Needs-Based Training Management Model for Educational Units in Preparing Teaching Modules on the Merdeka Mengajar Platform for PAUD Teachers - Jaya S, Togi Van; Arif, Syamsul; Yusnadi, Yusnadi (RIRAI Publisher, 2024)
The study aims to analyze the development process, effectiveness, and feasibility of the training management model based on the needs of educational units in compiling teaching modules on the Merdeka Teaching platform for PAUD teachers. This study uses the Research and Development (R&D) method using the ADDIE model. The collection technique uses a Likert scale questionnaire, an open questionnaire, a discussion note format, and an observation sheet. The data analysis technique is descriptive analysis, model feasibility test analysis, and model effectiveness analysis. The results of the model feasibility were obtained from the expert validation results with a score of 3.49 in the Very Good category, indicating that the training management model based on the needs of educational units in compiling teaching modules on the Merdeka Teaching platform for PAUD teachers is suitable for use in schools. Finally, the model effectiveness test can significantly improve teachers' ability to compile teaching modules, with an average pre-test score of 59 and an increase during the post-test with an average of 93 and a gain test result of 0.82, which is categorized as high. Thus, the effective needs-based training model can improve teachers' ability to compile teaching modules for PAUD teachers at the work center of the Pantai Labu District Cluster, Deli Serdang Regency.